Design of a Planar Tri-Band Notch UWB Antenna for X-Band, WLAN, and WiMAX - Alotaibi, S.; Alotaibi, A. A. (Engineering, Technology & Applied Science Research, 2020)
In this work, a new ultra-wideband (UWB) antenna design with 2.08GHz to 12GHz impedance bandwidth and triple-band specifications is presented. The proposed antenna is formed by a truncated square patch, a partial ground plane, and a 50Ω microstrip line. Three different types of slots were used in order to induce notched bands. A C-shaped slot is etched on the radiating patch to obtain a notched band in 3.31-4.21GHz for WiMAX. An inverted U-shaped slot in the micro-strip line induces a second notched band in order to reduce the interference with the WLAN [5.04-6.81GHz]. Finally, two inverted L-shaped slots around the micro-ribbon line on the ground plane allow the X-band [9.13 to 10.75GHz]. The antenna has dimensions of 32×28×1.6mm3. The Ansoft software (HFSS) was used to simulate the proposed structure. The simulation results are in good agreement with the measurement results. The antenna shows an omnidirectional radiation pattern.